2010
DOI: 10.1292/jvms.09-0235
|View full text |Cite
|
Sign up to set email alerts
|

A Case Resport of an Uncommon Sex-Cord Stromal Tumor Consisted of Luteal and Sertoli Cells in a Spayed Bitch

Abstract: ABSTRACT. We report a rare case of benign sex cord-stromal tumor consisted largely of luteoma with minor portion of Sertoli cell tumor located at the position of the left ovary excision in an 11-year-old ovariectomized bitch. Granulosa cell component was lacking, and both luteal and Sertoli cell portions were entirely positive for inhibin  and neuron-specific enolase, whereas luteoma portion alone was positive for Wilms' tumor-1 (WT1), immunohistochemically. The results suggest that this tumor is a possible c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
5
1
Order By: Relevance
“…Ovarian tumors in bitches are the result of neoplastic transformation of epithelial, germinal, or stromal cells [ 24 ]. Ovarian tumors of epithelial origin are more frequent than tumors of germinal [ 30 ] or stromal [ 16 20 24 ] cell origin. Epithelial-origin tumors include epithelial cell tumors, tumors of rete ovary, and of subepithelial structures such as papillary adenoma, papillary carcinoma, cyst adenoma, cyst adenocarcinoma, and non-differentiated carcinoma [ 10 11 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian tumors in bitches are the result of neoplastic transformation of epithelial, germinal, or stromal cells [ 24 ]. Ovarian tumors of epithelial origin are more frequent than tumors of germinal [ 30 ] or stromal [ 16 20 24 ] cell origin. Epithelial-origin tumors include epithelial cell tumors, tumors of rete ovary, and of subepithelial structures such as papillary adenoma, papillary carcinoma, cyst adenoma, cyst adenocarcinoma, and non-differentiated carcinoma [ 10 11 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there have been few reports on the expression of canine WT1 (cWT1) in dogs [ 7 , 8 , 17 ], and none of those reports was related to canine tumors. Therefore, evaluation of cWT1 expression in canine tumors will be helpful in the development of immunotherapy for dogs.…”
mentioning
confidence: 99%
“…This was consistent with the description in the product specification, where the antigen binding site of 6F-H2 is located at the N-terminal amino acids 1–181 of the human WT1 and is expected to bind to cWT1. A previous report has used a polyclonal antibody against human WT1 for IHC in canine tissue specimens, but the specificity of the antibody to cWT1 was never shown [ 7 ]. Western blotting of canine cell lines carried out in our lab using an anti-human WT1 polyclonal antibody (C-19) has revealed multiple non-specific bands (data not shown).…”
mentioning
confidence: 99%
“…The neoplasia is occasionally reported in intact bitches (20) but is very rare in spayed female dogs. Ichimura et al (8) recently reported a luteal and Sertoli cell tumour in a spayed bitch. Histogenetically, the neoplasma in the present case may have one of the four following origins: a) hermaphroditism, b) ectopic ovary, c) ovarian remnant syndrome and d) embryologic genetic defect.…”
Section: Discussionmentioning
confidence: 99%